Finger‐In‐Glove Sign in Congenital Bronchial Atresia - Jiuyang Xu; Haihong Gong; Run Tong; Min Liu; Xiaojing Cui (Respirology Case Reports)
ABSTRACT A previously healthy 45‐year‐old female presented with intermittent cough. Chest computed tomography showed finger‐in‐glove sign. Blood tests for fungal infection and cancer biomarkers were negative. Diagnostic bronchoscopy revealed bronchial atresia. Although most congenital lung malformations are diagnosed during pregnancy and childhood, they should be considered for differential diagnosis in adults.